2006
DOI: 10.1007/s11373-006-9117-3
|View full text |Cite
|
Sign up to set email alerts
|

The tumor-growth inhibitory activity of flavanone and 2′-OH flavanone in vitro and in vivo through induction of cell cycle arrest and suppression of cyclins and CDKs

Abstract: Natural products, including flavonoids, are suggested to be involved in the protective effects of fruits and vegetables against cancer. However, studies concerning the effect of flavonoids frequently lacked data regarding to flavanones. In this study, we investigated the inhibitory effect of flavanone compounds, including flavanone, 2'-OH flavanone, 4'-OH flavanone, 6-OH flavanone, naringin and naringenin, on cell growth of various cancer cells. We determined that flavanone and 2'-OH flavanone inhibited cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 40 publications
2
32
0
1
Order By: Relevance
“…2'-OH Flavanone was once again the compound with the highest inhibition rates by triggering apoptosis and increasing p21. A very similar study was carried out by Hsiao et al [229] in 2007, where various flavanones were screened against human lung adenocarcinoma, Lewis lung adenocarcinoma, murine lung adenocarcinoma, human gastric epithelial adenocarcinoma and human hepatocellular …”
Section: Flavanonesmentioning
confidence: 86%
“…2'-OH Flavanone was once again the compound with the highest inhibition rates by triggering apoptosis and increasing p21. A very similar study was carried out by Hsiao et al [229] in 2007, where various flavanones were screened against human lung adenocarcinoma, Lewis lung adenocarcinoma, murine lung adenocarcinoma, human gastric epithelial adenocarcinoma and human hepatocellular …”
Section: Flavanonesmentioning
confidence: 86%
“…Previous studies have shown that flavonoids with or without a single OH group had different effects on the viability of cancer cells [38]. Moreover, the presence of hydroxyl group in the structure of the flavonoids and the resonance of electrons between the A and B rings are very important for their biological activities [37,39,40]. According to previous studies and ours, we concluded that 3-HF might have a greater inhibitory effect on different cell lines compared to other dihydroxyflavones with a single OH group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, naringin, a flavonone similar to hesperetin found in citrus species, when administered prior to DOX, acts as the dual modulator of P-gp expression, and it was hypothesized that this may be an attractive new agent for the chemosensitization of cancer cells [47]. Further, it has been reported that flavonone along with anticancer drug, DOX, showed inhibitory effect on the growth of A549 lung cancer cells as well as on Lewis lung carcinoma [48]. Hesperetin significantly induces G1-phase cell cycle arrest in human breast cancer MCF-7 cells through the regulation of CDK4 and p21 (Cip 1) pathways [49].…”
Section: Discussionmentioning
confidence: 99%